Synthesis of carbon dots based on corn cobs as heavy metal ion sensors using the microwave method - Riski Intan Prasasti; Rihlatul Jannah; Annisa Nur Buana Wati; Kusumandari Kusumandari; Isnaeni Isnaeni (Universitas Sebelas Maret, 2022)
Carbon dots (CDots) are nanomaterials that can be applied as a heavy metal ion sensor. CDotss ware synthesized from corncobs which are abundant and underutilized. This study aims to determine the effect of variations in the concentration of corncobs on optical properties of CDots and their application as Fe3+ ion sensors. CDots were synthesized with variations of corncobs’ mass 5, 10, 15, and 20 g and variations in metal ion concentrations 10-7, 10-6, 10-5, 10-4, and 10-3 M. The success of CDots synthesis was indicated by luminescence green when exposed to UV light. UV-Vis characterization showed that the greater the concentration of CDots could cause a shift in the absorbance peak towards longer wavelengths and peaks at wavelengths of 290, 291, 295, 298, and 323 nm, respectively. Photoluminescence (PL) characterization showed CDots emission peaks at 511, 504, 503, and 495 nm. The greater the concentration of CDots can cause a shift in the emission peak towards a shorter wavelength and increase the intensity. The PL characterization can identify the presence of Fe3+ metal ions with a wavelength shift that indicates a change in the CDots structure. The synthesis of CDots from corncobs have great potential to be applied as sensors.